SAT062 Inhibition Of GIPR Expression Enhances Sulfonylurea-induced Insulin Secretion, And It Was Associated With Changes In ATP Contents - Ah Kim, Hyun; Yoon Lim, Ji; Seung Jung, Hye (Journal of the Endocrine Society, 2023)
Disclosure: H. Kim: None. J. Lim: None. H. Jung: None. Introduction: Sulfonylurea (SU) might be indispensable for a subset of patients with type 2 diabetes. In our previous study, we collected some patients who were extremely sensitive to SU for optimal glycemic control, then drew several candidate single nucleotide variants (SNV) using whole exome sequencing. Among them, 3 SNV (rs550405192, rs13306403, and rs13306402) were harbored by GIPR, coding a receptor for gastric inhibitory polypeptide 1-2). Therefore, in vitro study of GIPR on insulin secretory response to SU was performed in this study. Method:Gipr silencing was done in INS-1 cells using siRNA transfection. To induce glucolipotoxicity, 15-mM glucose and 150-uM palmitic acid were treated to the cells for 24 hours. Glimepiride (50 nM) was treated for 30 min in KRBH buffer with low-/high-glucose, following low-glucose starvation. Intracellular ATP contents and released ATP were measured with a bioluminescence assay kit. Quantitative RT-PCR to assess Vdac1 expression. Results:Gipr silencing was confirmed by reduced expression of mRNA and protein. GIP-induced insulin secretion was also down-regulated. Gipr silencing did not affect either basal or glucose-stimulated insulin secretion. As for SU-induced insulin secretion, Gipr silencing significantly increased it in a low-glucose condition (2.8 mM) but not in a high-glucose (17.5 mM). However, after chronic exposure to glucolipotoxicity, Gipr silencing significantly enhanced the response to SU in a high-glucose condition, too. These effects of Gipr silencing on the SU response were associated with changes in cellular ATP contents, which is critical to SU effects. Because diabetic condition had been reported to induce Vdac1 expression and subsequent ATP release in insulin-secreting cells3), we examined them with regard to Gipr silencing. Vdac1 expression was significantly increased when exposed to glucolipotoxicity, and Gipr silencing inhibited both Vdac1 expression and ATP release in the condition. Conclusion: According to the suppression of Vdac1 expression and ATP release by Gipr silencing in INS1 cells under glucolipotoxicity, interference of GIPR signaling would enhance SU-induced insulin secretion by preservation of cellular ATP. This study supported that loss-of-function mutations in GIPR as novel candidates regarding to sensitivity to SU in type 2 diabetes. References: 1) Min, Se Hee et al. “Clinical Characteristics of Subjects with Sulfonylurea-Dependent Type 2 Diabetes.” Endocrinology and metabolism (Seoul, Korea) vol. 30,4 (2015): 509-13. 2) KIM, Hyun Ah et al. “Inhibition of Gipr Enhanced Insulin Secretory Response to Sulfonylurea.” Abstract submitted to IDF Congress 2022 (Lisbon, Portugal). 3) Zhang, Enming et al. “Preserving Insulin Secretion in Diabetes by Inhibiting VDAC1 Overexpression and Surface Translocation in β Cells.” Cell metabolism vol. 29,1 (2019): 64-77.SNUHresearch funds (0320150420, 0420190600) and NRF grant (2022R1A2C2004570) by theMinistry of Science and ICT, Korea Presentation: Saturday, June 17, 2023